Combination of Nutmeg Seed (Myristica fragrans Houtt.) and Lemongrass (Cymbopogon citratus) Essential Oils: Evaluation of Antioxidant and Antibacterial Activities - Enny Fachriyah; Tyara Qisti Aisyah; Muhammad Badrul Huda (Jurnal Kimia Sains dan Aplikasi, 2026)
Essential oils are secondary metabolites that exhibit various biological activities, such as antioxidants and antibacterial activities. This study aimed to evaluate the antioxidant and antibacterial activities of nutmeg seed (Myristica fragrans Houtt.) and lemongrass (Cymbopogon citratus) essential oils, as well as their combination. The essential oils were obtained by steam distillation, physically characterized, and their chemical components analyzed using GC-MS. Antioxidant activity was determined using the DPPH method, and antibacterial activity was evaluated using the well-diffusion method against E. coli and S. aureus. The results showed that nutmeg seed essential oil contained α-pinene (18.49%) as the major compound with moderate antioxidant activity (IC50 = 139.49 mg/L), whereas lemongrass essential oil was dominated by α-pinene (29.19%) with lower antioxidant activity (IC50 = 263.54 mg/L). In antibacterial assays, nutmeg essential oil showed moderate to strong activity, while lemongrass essential oil exhibited weak to moderate activity. Among the combinations, the ratio of 2:1 (nutmeg:lemongrass) demonstrated the highest antibacterial activity, with inhibition zones of 13.50 mm against E. coli and 14.00 mm against S. aureus at 50% concentration, indicating improved antibacterial effects compared to other combinations. The combined essential oils of nutmeg and lemongrass exhibited bacteriostatic activity and showed improved antibacterial effects; however, no enhancement in antioxidant activity was observed.